RELIABLE AND EFFICIENT PARALLEL COMPUTING ON THE BASE OF MULTIAGENT SYSTEM - Otwagin, Aleksej (International Journal of Computing, 2014)
Basic principles of reliable parallel computations are considered. The parallel program is represented as a graph computation schema, that executed by unreliable computing system with possible node faults. For organization and optimization of parallel processing a kind of multiagent architecture was used. The proposed solution uses the principles of runtime evolutionary optimization to increase performance characteristics.